2020
DOI: 10.21831/cp.v39i3.32304
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Online Teaching: Early Childhood Education Lecturers' Perception of Barrier and Pedagogical Competency

Abstract: In this COVID-19 situation, online learning has been widely implemented in higher education contexts. This issue inspires the researchers to conduct further study on barriers encountered by lecturers in higher education. This study was carried out to explore how the lecturers perceive the barriers in online teaching practices and the level of pedagogical competencies perceived by the lecturers in conducting online learning in this emergency. The study employed a cross-sectional survey research design. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
1
31
0
10
Order By: Relevance
“…Their research result stated that the teachers are implementing online teaching positively and actively involved in forming students' future during lockdown period and young teachers are more actively participated in online teaching because of being more familiar with technology. Previous research also conducted by (Diningrat et al, 2020) about lecturers' perception of early childhood education toward the barriers of online teaching and pedagogic competence, the results indicated that the crucial barriers in the emergency of online teaching were limited connection and bandwidth, lack of students active participation and feedback, computer viruses, quality of material and online assessment.…”
Section: Introductionmentioning
confidence: 90%
“…Their research result stated that the teachers are implementing online teaching positively and actively involved in forming students' future during lockdown period and young teachers are more actively participated in online teaching because of being more familiar with technology. Previous research also conducted by (Diningrat et al, 2020) about lecturers' perception of early childhood education toward the barriers of online teaching and pedagogic competence, the results indicated that the crucial barriers in the emergency of online teaching were limited connection and bandwidth, lack of students active participation and feedback, computer viruses, quality of material and online assessment.…”
Section: Introductionmentioning
confidence: 90%
“…To prevent the spread of Covid-19, one of the policies issued was an appeal to always be at home (Piquero et al, 2020), which automatically resulted in the closure of schools around the world (Abdollahi et al, 2020;Panovska-griffiths et al, 2020;Pramling et al, 2020). As a solution, learning, which is usually presented face-to-face, is now served online (Diningrat et al, 2020).…”
Section: Adaptive Learning Strategies In Emergency Remote Teachingmentioning
confidence: 99%
“…Such rapid transformation has resulted in the unprepared ness of the teaching staff in preparing quality learning designs, so that the ongoing learning model is an unplanned alternative method for delivering course material over a long distance. This learning model is called emergency remote teaching (Bawa, 2020;Diningrat et al, 2020;Hussein et al, 2020). Almost all educational institutions throughout the country apply the emergency remote teaching model to carry out learning activities during this crisis period.…”
Section: Adaptive Learning Strategies In Emergency Remote Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada masa awal diberlakukannya study from home adanya hambatan berupa sistem pembelajaran yang belum siap, kurangnya sinergitas orang tua dengan pendidik sehingga banyak sekolah yang bingung, bahkan banyak sekolah meliburkan peserta didik (Diningrat et al, 2020). Meliburkan di sini artinya anak tidak berangkat sekolah dan tidak diberi tugas, sehingga pembelajaran terhenti.…”
unclassified